2018
DOI: 10.3390/ijms19103279
|View full text |Cite
|
Sign up to set email alerts
|

The Dominant Role of Forkhead Box Proteins in Cancer

Abstract: Forkhead box (FOX) proteins are multifaceted transcription factors that are significantly implicated in cancer, with various critical roles in biological processes. Herein, we provide an overview of several key members of the FOXA, FOXC, FOXM1, FOXO and FOXP subfamilies. Important pathophysiological processes of FOX transcription factors at multiple levels in a context-dependent manner are discussed. We also specifically summarize some major aspects of FOX transcription factors in association with cancer resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 218 publications
(209 reference statements)
2
65
0
2
Order By: Relevance
“…Moreover, dysregulation of FOXM1 is linked with the development of cancer drug resistance (Koo et al, 2012;Bach et al, 2018). Due to its regulatory role, during cancer progression FoxM1 constitutes an important target in cancer treatment (Bach et al, 2018). Treatment with nitroxoline at 20, 30 and 40 µM significantly reduced both FOXM1 mRNA and protein levels in vitro on HuCCT1 cells in dose-and time-dependent manners as was shown using qPCR and western blot analysis.…”
Section: Antitumor Activity Of Nitroxolinementioning
confidence: 80%
See 3 more Smart Citations
“…Moreover, dysregulation of FOXM1 is linked with the development of cancer drug resistance (Koo et al, 2012;Bach et al, 2018). Due to its regulatory role, during cancer progression FoxM1 constitutes an important target in cancer treatment (Bach et al, 2018). Treatment with nitroxoline at 20, 30 and 40 µM significantly reduced both FOXM1 mRNA and protein levels in vitro on HuCCT1 cells in dose-and time-dependent manners as was shown using qPCR and western blot analysis.…”
Section: Antitumor Activity Of Nitroxolinementioning
confidence: 80%
“…Forkhead box protein M1 (FOXM1) has been also recognized as target for nitroxoline antitumor activity (Chan-On et al, 2015). FOXM1 is an oncogenic transcription factor belonging to the Forkhead box (FOX) family, with a conserved winged-helix DNA-binding domain or forkhead domain (Bach et al, 2018;Koo et al, 2012). Proteins from the FOX family play an important regulatory role during embryogenesis and development (Bach et al, 2018) and are commonly upregulated in various types of cancer (Bach et al, 2018;Koo et al, 2012).…”
Section: Antitumor Activity Of Nitroxolinementioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, it has been reported that the FOXA family serves as both tumor suppressors and oncoproteins. FOXA1 is amplified and over-expressed in esophageal, lung, prostate and breast cancers, whereas loss of FOXA1 expression is linked to late-stage bladder cancer and aggressive tumor proliferation (Bach et al, 2018;Lam, Brosens, Gomes, & Koo, 2013). It is possible that FOXB2 also has functions as both tumor suppressors and oncopro teins.…”
Section: Genes To Cellsmentioning
confidence: 99%